Urinary sodium excretion is low prior to acute kidney injury in patients in the intensive care unit - de Morais, David Gomes; Sanches, Talita Rojas Cunha; Santinho, Mirela Aparecida Rodrigues; Yada, Eduardo Yuki; Segura, Gabriela Cardoso; Lowe, Diogo; Navarro, Guilherme; Seabra, Victor Faria; Taniguchi, Leandro Utino; Malbouisson, Luiz Marcelo Sá; de André, Carmen Diva Saldiva; Andrade, Lúcia; et al. (Frontiers in Nephrology, 2022)
Background Acute Kidney Injury (AKI) incidence is high in intensive care unit (ICU), and better understanding of AKI is needed. Early chronic kidney disease courses with urinary concentration inability and AKI recovery with increased urinary solute in humans. If kidney incapacity of urinary concentration and lower solute excretion could occur prior to diagnosis of AKI is still uncertain, and mechanisms associated have not been studied. Methods In this single-center prospective observational study, high AKI-risk ICU patients were followed up to 7 days or ICU discharge and posteriorly grouped as ‘AKI’ or ‘No AKI’ according to AKI status over admission. We collected daily urine samples to measure solutes and osmolality. Data were analyzed one day before AKI, or over first to fifth admission days in ‘No AKI’ group. We used logistic regression models to evaluate influence of variables on future AKI diagnosis. Kidney transporters expression in urine were evaluated by Western blot. Results We included 29 patients as ‘No AKI’ and 23 patients as ‘AKI’, mostly low severity AKI. Urinary sodium excretion was lower in ‘AKI’ patients prior to AKI diagnosis, particularly in septic patients. Urinary sodium transporter NHE3 expression was higher in ‘AKI’ patients. Conclusions Urinary sodium excretion is low before an AKI episode in ICU patients and high proximal tubule sodium transporter might contribute to this.